Elevating Security with Arm CCA. - Garcia-Tobin, Charles; Knight, Mark (Communications of the ACM, 2024)
Confidential computing offers significant potential to enhance the security of computing platforms by minimizing the trusted computing base (TCB) and reducing attack surfaces. It relies on innovations in both hardware and software to enable secure operation, particularly those managed by third parties. Attestation and verification mechanisms are essential for establishing trust in confidential computing, and as adoption grows, certifiers and regulators may play a larger role in guiding consumer decisions.